Equivalent circuit parameter extraction of low‐capacitance high‐damping PTs. Issue 7 (1st March 2020) - Forrester, J.; Li, L.; Davidson, J.N.; Foster, M.P.; Stone, D.A.; Sinclair, D.C.; Reaney, I.M.
Abstract : Existing equivalent circuit extraction techniques are inaccurate for piezoelectric transformers (PTs) with low‐input capacitance or high damping. A new method is presented, offering improved accuracy in both damping resistance and resonant frequency extraction compared with state‐of‐the‐art methods. Effectiveness is evaluated on two sample PTs, with the proposed method achieving up to 84% decrease in error compared with previous methods.